MANAJEMEN AKTIVITAS TEMPAT PELELANGAN IKAN DALAM PENJUALAN HASIL TANGKAPAN NELAYAN PADA TEMPAT PELELANGAN IKAN OEBA DI KELURAHAN FATUBESI, KECAMATAN KOTA LAMA, KOTA KUPANG - Franciskus Dalu Bentu; Eusabius Separera Niron; Yohana Fransiska Medho (Journal Education and Government Wiyata, 2025)
This research is titled "Operational Management of the Fish Auction Function in Selling Fishermen's Catch at the Oeba Fish Auction Place in Fatubesi Village, Kota Lama District, Kupang City." The main objective of this research is to explain the operational management issues at the Oeba Fish Auction Place. The research method used is descriptive qualitative with techniques of interviews, observation, and documentation. The research results indicate that the management of the Oeba Fish Auction Place is not functioning well. First, the planning system lacks specific regulations and well-developed SOPs. Second, the organization is ineffective due to the lack of budget from the NTT Marine and Fisheries Office. Third, the implementation is not optimal, resulting in unachieved revenue targets. Fourth, the lack of supervision and efforts to improve human resources have caused the issue of illegal foreign fishing vessels to persist.